Chloride Hexahydrate Iontophoresis with Topical Application of It in Primary Palmar Hyperhidrosis - A Zeinalzade; KH Khademi; F Kobarfard; S Nazary (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2010)
BACKGROUND AND OBJECTIVE: Sweating greater than the physiological needs of the body is hyperhidrosis. The patient who suffers from palmar hyperhidrosis faces social, occupational and psychological problems. Topical application of aluminium chloride hexahydrate on affected area was considered as effective treatment for palmar hyperhidrosis. But no study has been published yet about the iontophoresis of this solution for treatment of palmar hyperhidrosis. The aim of this study was to compare the efficacy and persistency of aluminum chloride hexahydrate iontophoresis with topical application of it on the patients with primary palmar hyperhidrosis. METHODS: This clinical trial study was performed on 12 patients aged 20-32 years. Iontophoresis of aluminium chloride hexahydrate was applied on experimental hand for 30 minutes in 4 sessions and topical aluminium chloride hexahydrate was applied on control hand with the same dose and duration. Before treatment Gravimetry and iodine–starch test were performed to evaluate the rate of sweating production. All patients filled out Dermatology Life Quality Index questionnaire to determine amount of impairment in quality of life. All patients underwent a pretreatment and post treatment evaluation at 3 days, 1, 2, 3 and 4 weeks after the treatment. FINDINGS: Sweating rate significantly decreased in experiment group 3 days later from 0.46±0.02gr to 0.10±0.01 gr, 1 week later to 0.19±0.03 gr, 2 weeks Later to 0.21±0.05 gr, 3 weeks later to 0.26±0.10 gr and 4 weeks later to 0.27±0.15 gr (p<0.05) and in control group decreased 3 days later from 0.54±0.18 gr to 0.10±0.08 gr, 1 week later to 0.22±0.15 gr, 2 weeks later to 0.28±0.12 gr, 3 weeks later to 0.35±0.20 gr (p<0.05). CONCLUSION: The results indicate that iontophoresis of Al cl3 induced reduction of sweating rate for at least 1 month without any side effects. The persistency of effects in this method is longer than topical application of Al cl3.